Empowering Students to Take Control Through Student Leadership Teams - Andrea Gratton; Kyle Chadburn (Middle Grades Review, 2019)
As our educational system becomes more focused on personalizing learning for students, it is increasingly important for educators to empower students to take an active role in their learning and their communities. In this practitioner perspective, two educators reflect on the process of establishing student leadership teams in their school, and on the research that supports such efforts toward developing systems of student agency and self-advocacy in education.
Keywords: middle school; middle grades; early adolescence; young adolescents; student voice; student agency; student leadership